2017
DOI: 10.1007/s13593-017-0469-z
|View full text |Cite
|
Sign up to set email alerts
|

Preceding crops influence agronomic efficiency in sugar beet cultivation

Abstract: The choice of the crop succession influences the agronomic efficiency (yield per unit agronomic input) and is relevant for the sustainable intensification of crop cultivation. However, such effects are often ignored in assessments of agronomic efficiency. The aim of the study was to propose a concept for the assessment of and to publish data on (i) the effect of the preceding crop on the amount of agronomic inputs used and the yield in sugar beet cultivation and (ii) the agronomic efficiency of the 2-year sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
7
0
4
Order By: Relevance
“…Quality and amount of crop residue and its effects on soil microbial processes, residue decomposition, and soil mineralization are some factors that can affect subsequent crops (Sawyer and Mallarino, 2017). Our result aligns with Jacobs et al (2018) that demonstrated that sugar beet following grain pea had lower N requirement, and subsequently higher N use efficiency compared to sugar beet following silage maize.…”
Section: Inter-annual Variationsupporting
confidence: 91%
“…Quality and amount of crop residue and its effects on soil microbial processes, residue decomposition, and soil mineralization are some factors that can affect subsequent crops (Sawyer and Mallarino, 2017). Our result aligns with Jacobs et al (2018) that demonstrated that sugar beet following grain pea had lower N requirement, and subsequently higher N use efficiency compared to sugar beet following silage maize.…”
Section: Inter-annual Variationsupporting
confidence: 91%
“…This may be effective for a prolonged period of time and affect the next plant growing in the same soil ( Lapsansky et al, 2016 ). Agronomically, a preceding crop can affect the yield of a following crop ( Jacobs et al, 2018 ). Understanding plant-microbiome feedbacks was suggested to be one of the keys for exploiting the yield potential of cropping systems ( Ahkami et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Загалом економічна ефективність виробництва цукрових буряків визначається цілою низкою показників, серед яких основними є врожайність, продуктивність праці, собівартість продукції, ціни, рентабельність і розмір прибутку з одиниці посівної площі [22].…”
Section: вступunclassified